Transport and chemical kinetics of H2/N2 jet flame: A flamelet modelling approach with NOx prediction - Alim, MA; Malalasekera, W (Journal of Naval Architecture and Marine Engineering, 2009)
Â In this work simulation of a turbulent H2/N2 jet diffusion flame with flamelet modelling has been presented. The favre-averaged mixture fraction has been employed to model the combustion. Favre-averaged scalar quantities have been calculated from flamelet libraries by making use of a presumed Probability Density Function (PDF) method. The predicted flame temperature profiles and chemical species concentrations are compared with TNF experimental data obtained from Sandia/California. Predictions considering the unity Lewis number flamelet are found to be in good agreement with temperature and chemical species measurements. Predicted NO results also compared and shown with other species. This study shows that the combustion simulation using unity Lewis number flamelets are effective for predicting the flow, temperature and chemical kinetics of H2/N2 diffusion flame. To account for fluctuations of mixture fraction, its distribution is presumed to have the shape of a beta-function. Keywords: Non-premixed flame, Turbulent Combustion, Flamelet modelling Â doi: 10.3329/jname.v2i1.2028 Journal of Naval Architecture and Marine Engineering 2(1)(2005)33-40